2011
DOI: 10.1186/1750-1172-6-65
|View full text |Cite
|
Sign up to set email alerts
|

Mutational screening of the USH2A gene in Spanish USH patients reveals 23 novel pathogenic mutations

Abstract: BackgroundUsher Syndrome type II (USH2) is an autosomal recessive disorder, characterized by moderate to severe hearing impairment and retinitis pigmentosa (RP). Among the three genes implicated, mutations in the USH2A gene account for 74-90% of the USH2 cases.MethodsTo identify the genetic cause of the disease and determine the frequency of USH2A mutations in a cohort of 88 unrelated USH Spanish patients, we carried out a mutation screening of the 72 coding exons of this gene by direct sequencing. Moreover, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 42 publications
2
39
0
2
Order By: Relevance
“…28 Participant 12 with late onset RP had two missense variants of unknown significance, c.7130A>G (p.Asn2377Ser) and c.11927C>T (p.Thr3976Met), which have both previously been reported. 28-30 …”
Section: Discussionmentioning
confidence: 99%
“…28 Participant 12 with late onset RP had two missense variants of unknown significance, c.7130A>G (p.Asn2377Ser) and c.11927C>T (p.Thr3976Met), which have both previously been reported. 28-30 …”
Section: Discussionmentioning
confidence: 99%
“…It is often not possible to identify both pathogenic variants in USH2A [6-8]. In this study we identified eight mutations in 23 USH2 families (35%) who were known to have a monoallelic pathogenic/UV4/UV3 mutations in USH2A detected by Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Usher type 2 is the most prevalent form accounting for more than half of reported cases. There are three genes underlying USH2: USH2A, GPR98 and DFNB31 ( WHRN) , with USH2A accounting for 75-80% of cases [6-8]. The mutational spectrum of USH2A is diverse and includes nonsense, frameshift, missense and splice-affecting mutations, as well as deletions and small duplications [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations